APP TO EVALUATE THE LEVEL OF CONSCIOUSNESS IN ADULTS: TECHNOLOGICAL PRODUCTION IN NURSING. - Tomaz dos Santos Barros, Wanessa Cristina; Marcon Dal Sasso, Grace Terezinha; Alvarez, Ana Graziela; Ramos, Saulo Fábio; Martins, Sabrina Regina (Cogitare Enfermagem, 2019)
Objective: to develop an app for assessing the level of consciousness in adults. Method: technological production, structured from the theoretical framework of problem-based learning methodology and developed considering the steps of contextualized instructional design (analysis, design, development, evaluation). Study conducted at the Federal University of Santa Catarina, from May 2014 to April 2015. Results: the app presents the contents: scales for evaluation of the level of consciousness, pupillary evaluation, reflexes and breathing pattern, presented to the users through short texts with brief explanations, images and videos. Conclusion: the app can facilitate the study of the theme at any time or place, even allowing its application at the bedside, thus contributing to improvements in teaching, care and safety of critically ill patients. The results of the evaluation of the technology by teachers and students will be the object of future studies.